2019
DOI: 10.1039/c9nr07117b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating ligand effects in thiolate-protected metal clusters using Au24Pt(TBBT)18 as a model cluster

Abstract: 2-Phenylethanethiolate (PET) and 4-tert-butylbenzenethiolate (TBBT) are the most frequently used ligands in the study of thiolate (SR)-protected metal clusters. However, the effect of difference in the functional group between these ligands on the fundamental properties of the clusters has not been clarified. We synthesized [Au 24 Pt(TBBT) 18 ] 0 , which has the same number of metal atoms, number of ligands, and framework structure as [Au 24 Pt(PET) 18 ] 0 , by replacing ligands of [Au 24 Pt(PET) 18 ] 0 with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 67 publications
2
51
0
Order By: Relevance
“…Pure oxidation or reduction improved activity at 250 °C, but the maximum and lower temperature activity was obtained by a combination of oxidation and reduction (pretO 2 –H 2 ). Oxidation allows for removal of ligands 49 , 74 and surface impurities (synthesis residues), while the subsequent H 2 treatment reduces oxidized Pd (and Au) atoms. 61 Activity set in at 225 °C, which agrees with CO oxidation on (impregnated) Pd/Al 2 O 3 catalysts (below 225 °C, the actives sites are poisoned by CO).…”
Section: Resultsmentioning
confidence: 99%
“…Pure oxidation or reduction improved activity at 250 °C, but the maximum and lower temperature activity was obtained by a combination of oxidation and reduction (pretO 2 –H 2 ). Oxidation allows for removal of ligands 49 , 74 and surface impurities (synthesis residues), while the subsequent H 2 treatment reduces oxidized Pd (and Au) atoms. 61 Activity set in at 225 °C, which agrees with CO oxidation on (impregnated) Pd/Al 2 O 3 catalysts (below 225 °C, the actives sites are poisoned by CO).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical compositiono ft he product strongly depends on the chemical properties of thiolate. [49,83] Thus, the thiolates in the same category (Scheme 1A-D) are typicallyu sed for obtaining the alloy NCs with the same numbers of metal atoms and ligands. In the following subsections, four representative synthesis methods of alloy NCs are outlined.…”
Section: Precise Synthesis Methodsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39]41] Similar researchh as recently been undertaken by several groups,a nd their findings have demonstrated that the mixing( alloying) of heteroelements is an extremelye ffective means to modulate the electronic structure and functions of NCs. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] In addition,…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the number of constituent atoms of metal NCs is controlled, it is possible to produce various physical/chemical properties and functions by using only one type of metal element. If several types of elements can be used, it becomes possible to obtain more functionalities [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. For these reasons, metal NCs have been attracting considerable attention as a central material in nanotechnology.…”
Section: Introductionmentioning
confidence: 99%